Lymphocyte Updates - Cancer, Autoimmunity and Infection 2017
DOI: 10.5772/intechopen.69346
|View full text |Cite
|
Sign up to set email alerts
|

B Lymphocyte as a Target of Bacterial Infections

Abstract: B lymphocytes are central players in the immune response; canonically, they have been recognized as precursors of antibody-producing cells: plasma cells. Recent findings have shown that the role of B lymphocytes goes far beyond the production of antibodies. There are different subtypes of B lymphocytes with different participations in innate and adaptive responses that include the recognition of the antigen, its processing, and its presentation to T lymphocytes, as well as the production of cytokines that impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 184 publications
0
3
0
Order By: Relevance
“…B1 cells produce IgM as natural antibodies independent from infection and are accountable for most of the circulating IgM, but can also actively respond to T cell-independent antigenic stimulation, especially to encapsulated bacteria ( 37 ). B1 cells are mobilized in response to pathogens and migrate to secondary lymphoid organs like lymph nodes, where they secrete IgM antibodies ( 52 ). Thus, B1 cells represent the first line of defense in bacterial infection and link innate and adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B1 cells produce IgM as natural antibodies independent from infection and are accountable for most of the circulating IgM, but can also actively respond to T cell-independent antigenic stimulation, especially to encapsulated bacteria ( 37 ). B1 cells are mobilized in response to pathogens and migrate to secondary lymphoid organs like lymph nodes, where they secrete IgM antibodies ( 52 ). Thus, B1 cells represent the first line of defense in bacterial infection and link innate and adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Typical examples are Epstein-Barr virus, cytomegalovirus, smallpox virus or Brucella , but also parasites like Trypanosoma ssp. or Plasmodium falciparum ( 52 , 55 57 ). The modulation of B cells by interfering with BCR signaling seems to be a less common strategy of pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Their signaling in B-cells is related to the stage of activation and the tissue situation of the B-cells ( 101 ). It has also been reported that certain receptors of the purinoceptor family, such as P2X7 and P2Y11, are expressed on B-cells ( 102 , 103 ).…”
Section: Can Antimicrobial Peptides Affect the Function Of B-cells In...mentioning
confidence: 99%